A study for obtaining more solitary pattern solutions of fifth-order KdV-like equations - İnç, Mustafa; Evans, DJ (Taylor & Francis Ltd, 2004)
In this article, we will investigate the solitary pattern solutions of the modified form of fifth-order KdV equations by using two direct formulations. Thus, we get new solitary pattern solutions having cusps or infinite slopes. In addition, new solitary wave and singular solitary wave solutions are obtained.
Keywords: mfK(m,n,k,p) equation; solitary pattern solution; solitary wave solution